Digital participation in traumatic brain injury: scoping review about assessment tools for computer-mediated communication - Büttner-Kunert, Julia; Royko, Julia; Resch, Katharina; Heider, Nathalie; Falkowska, Zofia (Frontiers in Communication, 2023)
Background: Individuals with chronic traumatic brain injury (TBI) are often affected by communication disorders which might have an impact on their social participation. Due to possible cognitive and communicative disabilities, as well as impairments of social cognitive skills, individuals with TBI (IwTBI) have been observed to exhibit difficulties in maintaining and establishing social relationships, resulting in a greater risk of social isolation. This applies to both inperson as well as computer-mediated communication (CMC), which is considered an integral part of everyday life. Research on digital participation in the TBI population has focused on the possible challenges and barriers, but also on the benefits of CMC for social interactions. However, there is no overview of whether the available instruments can capture digital aspects of participation or social media use in TBI. Aim: In this scoping review we aimed to provide an overview over currently available instruments that help assess CMC use as a measure of digital participation in the TBI population. Method: Relevant databases were screened for publications between the years 2013 and 2023 with relevant search terms referring to social participation, assessment tools, CMC and the target group, in order to find suitable tools to assess digital participation in IwTBI. In a multistage selection process following the PRISMA criteria, the instruments found were examined in terms of items that assess digital participation. The outcome of the review is an overview of the status quo of potentially available instruments that capture aspects of CMC. Results: Following a screening on title/ abstract and full-text level, a total of 10 studies could be identified that present assessment tools that evaluate CMC use as a measure of digital participation in the TBI population. Conclusion: Digital participation is an important aspect of everyday lives for IwTBI. CMC should be an integral part of rehabilitation. The existing appropriate questionnaires uncovered in the current study should be applied routinely to detect impairments in CMC and digital participation. Overall, however, there is still a great need for research in the field of CMC, both regarding methods for measuring digital participation disorders as well as resources.